Dilated Dense U-Net for Infant Hippocampus Subfield Segmentation - Zhu, Hancan; Shi, Feng; Wang, Li; Hung, Sheng-Che; Chen, Meng-Hsiang; Wang, Shuai; Lin, Weili; Shen, Dinggang (Frontiers in Neuroinformatics, 2019)
Accurate and automatic segmentation of infant hippocampal subfields from magnetic resonance (MR) images is an important step for studying memory related infant neurological diseases. However, existing hippocampus subfield segmentation methods were generally designed based on adult subjects and would compromise performance when applied to infant subjects due to insufficient tissue contrast and fast changing structural patterns of early hippocampal development. In this paper, we propose a new fully convolutional network (FCN) for infant hippocampus subfield segmentation by embedding the dilated dense network in the U-net, namely DUnet. The embedded dilated dense network can generate multi-scale features while keeping high spatial resolution, which is useful in fusing the low-level features in the contracting path with the high-level features in the expanding path. To further improve the performance, we group every two convolutional layers with one residual connection in the DUnet, and obtain the Residual DUnet (ResDUnet). Experimental results show that the proposed DUnet and ResDUnet improve the average Dice coefficient by 2.1% and 2.5% for infant hippocampus subfield segmentation, respectively, when compared with the 3D U-net. The results also demonstrate that the proposed methods outperform the state-of-the-art methods.